Image Reconstruction Enhancement Using Convolution Back Projection Method for Electrical Tomography Application - Pusppanathan, Jaysuman; Mansor, Muhammad Saiful Badri; Rahim, Ruzairi Abdul; Mohd Muji, Siti Zarina; Abdullah, Fatin Aliah Phang; Abdul Rahman, Nor Farahwahidah; Faramarzi, Mahdi (International Journal of Integrated Engineering, 2018)
This paper presents an image enhancement technique using convolution back-projection (CBP) technique to overcome the blurry issue caused by linear back-projection (LBP) technique on tomographic images. The CBP technique is discussed and employed on four different types of stratified flow test profiles. The obtained image results are compared between LBP and CBP and further assessed using mutual structural similarity index (MSSIM). The enhancement technique has successfully scored MSSIM rating above 0.9 for all four test profiles whereby the rating is ranging from 0 (poor quality) to 1 (best quality).